PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA BLOOKET TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR GUGUS V KECAMATAN GEROKGAK - Widi Astuti, Kadek Siska; Nirmayani, Heny; Sastrika Ayu, Putu Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low Pancasila Education learning outcomes among fifth-grade students at SDN Gugus V, Gerokgak District, caused by lecture-dominated teaching and limited innovative media, motivated this study. This research aimed to determine significant differences in Pancasila Education learning outcomes between students taught using the Game Based Learning model assisted by Blooket media and conventional learning. A quantitative quasi-experimental approach with Pretest-Posttest Control Group Design was employed. The sample consisted of 34 students from SDN 2 Musi as the experimental group and 28 students from SDN 2 Banyupoh as the control group. Independent t-test results yielded t-value = 7.579 with significance 0.000 < 0.05. The experimental group's posttest mean of 76.85 exceeded the control group's 45.18, with an N-Gain of 61.38% categorized as moderately effective. It is concluded that the Game Based Learning model assisted by Blooket media significantly influences Pancasila Education learning outcomes among fifth-grade students at SDN Gugus V, Gerokgak District.